Comparative Review of Rotary Friction Welding Between Aluminium and Copper Alloys for Enhanced Joint Strength - Riyan Ariyansah; Aditya Rio Prabowo; Nurul Muhayat; Bagus Anang Nugroho; Triyono Triyono (Engineering Proceedings, 2025)
This study evaluates and compares the effectiveness of friction stir welding on aluminium and copper alloys with the aim of improving the strength of the resulting joints. The rotary friction stir welding method was chosen for its ability to produce high-quality joints with minimal deformation. This study explores various welding parameters, such as rotating speed, welding speed, and tool design, and their impact on the mechanical properties of the joint, including tensile strength, hardness, and microstructure of the weld region. The findings show that the optimum parameters for aluminium and copper alloys differ significantly: the tensile strength of aluminium is around 240 MPa, while copper joints require careful adjustment to avoid defects, reaching around 220 MPa. Aluminium showed improved joint strength with higher rotating speed and welding speed parameters, while copper required more precise parameter adjustments to prevent cracking and other defects. The results of this study provide practical guidance for selecting appropriate rotary friction welding parameters to optimize joint strength in aluminium and copper alloys, which can enhance the application of these materials in industry.